Pengaruh Disiplin Kerja Terhadap Prestasi Kerja Pegawai Dinas Pendapatan Daerah Kutai Kartanegara - Andi Indra Irawan; Joko Sabtohadi; Mariani Madjid (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2019)
Abstract :The purpose of the analysis is to find out whether the work discipline variables have a significant influence on the work performance of the Regional Revenue Service staff of the Kutai Kartanegara Regency. The results of the research show that the work discipline variables have a significant influence on the work performance of employees of the Regional Revenue Service of Kutai Kartanegara acceptable truth, where the value of t count the work discipline variable is greater than the value of t table (16,332> 1,66055) with a significance value smaller than the significance level (0,000 <0,05). Thus the proposed hypothesis has been proven and acceptable.Keywords: work disciplin, work performance